Genome-Wide and Exome-Capturing Sequencing of a Gamma-Ray-Induced Mutant Reveals Biased Variations in Common Wheat - Li, Yuting; Xiong, Hongchun; Zhang, Jiazi; Guo, Huijun; Zhou, Chunyun; Xie, Yongdun; Zhao, Linshu; Gu, Jiayu; Zhao, Shirong; Ding, Yuping; Fang, Zhengwu; Liu, Luxiang (Frontiers in Plant Science, 2022)
Induced mutagenesis is a powerful approach for the creation of novel germplasm and the improvement of agronomic traits. The evaluation of mutagenic effects and functional variations in crops is needed for breeding mutant strains. To investigate the mutagenic effects of gamma-ray irradiation in wheat, this study characterized genomic variations of wheat early heading mutant (eh1) as compared to wild-type (WT) Zhongyuan 9 (ZY9). Whole-genome resequencing of eh1 and ZY9 produced 737.7 Gb sequencing data and identified a total of 23,537,117 homozygous single nucleotide polymorphism (SNP) and 1,608,468 Indel. Analysis of SNP distribution across the chromosome suggests that mutation hotspots existed in certain chromosomal regions. Among the three subgenomes, the variation frequency in subgenome D was significantly lower than in subgenomes A and B. A total of 27.8 Gb data were obtained by exome-capturing sequencing, while 217,948 SNP and 13,554 Indel were identified. Variation annotation in the gene-coding sequences demonstrated that 5.0% of the SNP and 5.3% of the Indel were functionally important. Characterization of exomic variations in 12 additional gamma-ray-induced mutant lines further provided additional insights into the mutagenic effects of this approach. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genome (KEGG) analysis suggested that genes with functional variations were enriched in several metabolic pathways, including plant–pathogen interactions and ADP binding. Kompetitive allele-specific PCR (KASP) genotyping with selected SNP within functional genes indicated that 85.7% of the SNPs were polymorphic between the eh1 and wild type. This study provides a basic understanding of the mechanism behind gamma-ray irradiation in hexaploid wheat.